Together for the Security: Interview with Dr. Tibor Takács, pol. major general, director general of the Counter-terrorism Information and Criminal Analyses Centre (Academic Journal of Internal Affairs, 2021)
The basic reason for foundation of the Counter-terrorism Information and Criminal Analyses Centre (further CICAC) in 2016 were the changes in the field of terrorism and criminality, first of all of organised criminality and extremist organisations, which required to set up an organisation that can support the decisions of the government by tactical and strategic analysis and proposals in overall security approach. This new type of task system, like information fusion and information sharing tasks, demands from colleagues of the new organisation a significantly more information conscious, and from their leaders a knowledge-management based cooperation and communication. This new organisation received a wide-ranging authorisation for fulfilment of tasks, it can gather data even by direct electronic data connection. Therefore, there are special competence requirements for colleagues of CICAC – beside the general requirements – an outstanding level of reliability, solid morality and loyalty to the organisation. All these aspects were not only reasonable but even necessary to take into consideration in formation of the new organisation management system of CICAC. The sustainable competitiveness of the new organisation demanded to lay down basics for a special, self-developing organisational culture at the earliest opportunity. For that was unavoidable that the continuously appearing new values at CICAC – especially organisational values – find expression in the daily practice, even that they become a solid value system. This value-based approach could result in development of – by now already clearly existing – integration community. Beyond that appeared as a prominent duty the formation of an effective and fruitful cooperation with partner organisations, emphasised with law enforcement organisations, with organisations of national security and of public service. Simultaneously the cooperation can only reach a high-level if its content and formal frames are clearly defined for and accepted by everybody. CICAC will celebrate its fifth anniversary this year. The organisation has chosen the slogan „Together for Security” for the five years jubilee. In this context, Dr. Tibor Takács, pol. major general, director general of CICAC was interviewed by Dr. Valér Dános, editor-in-chief of Belügyi Szemle.
Keywords: interview; security; counter-terrorism